Structural Changes in the Cell Wall of Schizosaccharomyces pombe During Cell Division - Streiblová, Eva (1966)
Streiblová, Eva (Czechoslovak Academy of Sciences, Prague, Czechoslovakia), I. Málek, and K. Beran. Structural changes in the cell wall of Schizosaccharomyces pombe during cell division. J. Bacteriol. 91:428–435. 1966.—Individual stages of growing and dividing cells of Schizosaccharomyces pombe were studied by means of fluorescence and electron microscopy with the use of metal-shadowed isolated walls, replicas, and ultrathin sections. Vegetative cells were found to contain division scars (six at the most); their formation and structure are described. More data on the growth of arthrospores were obtained. New structural observations were made on the architecture of the cell wall (original wall ring, polar cell wall, plug wall band, additional wall ring). Structural changes of cell surfaces and lateral walls during fission are represented schematically to the fourth generation. The question of origin of the septum is discussed, and on this basis the entire structure of the cell wall is interpreted.